Five little pumpkins - Van Rynbach, Iris (Honesdale, Pa. : Boyds Mills Press, 1995)
The traditional finger rhyme illustrated with watercolors.
SJ 10/95, PW 09/18/95, BL 09/15/95
0306
Keywords: Children's poetry; Finger play; Nursery rhymes